緊急胆道ドレナージにおけるステント留置の有用性 - Hirata Ikuhiro; 高橋 周史; Nakabe Nami; 坂元 直行; 朴 義男; 吉川 敏一 (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2007)
Rapid and safe biliary decompression is essential for the treatment of acute disease of the biliary tract. Endoscopic nasobiliary drainage (ENBD) is the conventionally used maneuver. Because we have encountered several instances of trouble, including displacement, with the use of drainage tubes, we have come to prefer another endoscopic method, namely, placement of plastic biliary stents. The present study discusses the usefulness of stent placement as compared with that of ENBD in patients with acute biliary disease. We retrospectively examined 32 patients treated by ENBD and 37 patients treated by stent placement at our center between January 2002 and December 2005. We investigated the patient backgrounds, outcomes of the drainage, complications and prognosis. The results revealed no significant differences in the patient backgrounds (the mean age, underlying diseases, etiology and pathology) of the two groups. ENBD and stent placement were equally effective, because the serum level of total bilirubin and CRP decreased almost equally in both the groups after 3 days of drainage. Tube failure occurred significantly frequently in patients treated by ENBD (31.3%) as compared to that in those treated by stent placement (2.7%). There was no difference in the prognosis between the two groups. Since endoscopic biliary stent placement is the same as ENBD in terms of effectiveness and more advantageous with regard to safety, we conclude that it may be considered as the first choice for emergency biliary drainage. 胆道救急疾患の治療において迅速・安全な胆道ドレナージは必要不可欠である。内視鏡的経鼻胆道ドレナージ (ENBD) は当センターではチューブトラブルが少なからず発生したため, 内視鏡的プラスチックステント留置を現在第一選択としている。そこでステント留置の有用性の評価のため, 2002年から2005年に当センターで施行したENBD群32例とstent群37例の患者背景・ドレナージ効果・偶発症・転帰につき比較検討した。その結果, 平均年齢, 有合併症率, 原因疾患と入院時病態の内訳に差は認めず, 両群の患者背景は同等だった。両群ともドレナージにより総ビリルビン値とCRP値の改善が同等に認められ, 病態改善効果に差はなかった。チューブトラブルは, ENBD群10例 (31.3%), stent群1例 (2.7%) であり, ENBD群に有意に多かった。処置後1ヵ月以内の死亡例は両群1例ずつだった。ENBD群の死亡例は, チューブトラブルに起因するものであった。以上より, 胆管ステント留置は, 経鼻胆道ドレナージと効果は同等で, 安全性は優位であり, 緊急胆道ドレナージ法として有用である。